Rola wychowawcza ojca w rodzinie rzymskiej według Plutarcha z Cheronei - Ciesielski, Mariusz (Studia Europaea Gnesnensia, 2014)
The paper is devoted to the educational role of the father in a Roman family as envisioned by Plutarch of Chaeronea in his notion of optimised moral and intellectual development of a boy and young man. Furthermore, the article depicts Roman realities and their relation to the “ideal” recommendations of the Chaeronean, in the context of transformation of morals and changes in methods of bringing up resulting from the expansive policy of Rome from the 3rd century BC to the 3rd century AD.